Pengaruh Peran Teknologi Blockchain terhadap Efisiensi Proses Pelaporan Keuangan dan Akuntansi pada Industri Perbankan di Indonesia - Judijanto, Loso; Sudarmanto, Eko; Ady Bakri, Asri; Susanto, Edy; Kalsum, Ummu (Sanskara Akuntansi dan Keuangan, 2024)
This research investigates the influence of blockchain technology on the efficiency of financial reporting and accounting processes in the banking industry in Indonesia. Through quantitative analysis involving 200 professionals from Indonesian banks and financial institutions, this research examines perceptions, correlations and predictive relationships related to blockchain adoption and financial process efficiency. These findings reveal a positive perception of blockchain's impact on financial processes, with higher levels of blockchain adoption associated with better efficiency metrics such as transaction processing time, data accuracy, and auditability. Regression analysis further confirms blockchain adoption as a significant predictor of financial reporting and accounting efficiency, even after controlling for organizational size, technological infrastructure, and regulatory environment. The results of this research underscore the transformative potential of blockchain technology in revolutionizing financial processes and driving operational excellence in banks in Indonesia.